Highly efficient extraction of actinides with pillar[5]arene-derived diglycolamides in ionic liquids via a unique mechanism involving competitive host–guest interactions. Issue 48 (22nd November 2016) - Li, Caixia; Wu, Lei; Chen, Lixi; Yuan, Xiangyang; Cai, Yimin; Feng, Wen; Liu, Ning; Ren, Yi; Sengupta, Arijit; Murali, Mallekav S.; Mohapatra, Prasanta K.; Tao, Guohong; et al.
Abstract : A novel extraction mechanism is described. Abstract : Actinide partitioning is considered as one of the most challenging issues in nuclear waste remediation. Herein, we unravel a novel extraction mode pertinent to the competitive host–guest interactions for highly efficient actinide extraction. The host–guest recognition event involves binding of a room temperature ionic liquid (RTIL), 1- n -octyl-3 methylimidazolium bis(trifluoromethane)sulfonamide (C8 mimNTf2 ), as both the guest and the solvent by the hosts pillar[5]arene-based diglycolamides (P5DGAs) and the subsequent displacement of the guest by a metal ion. This two-step process suggests a unique competitive ion-mediated displacement mechanism for the metal ion partitioning in the extraction process. The supramolecular extraction system is evaluated for its extraction abilities towards actinide ions such as UO2 2+, PuO2 2+, Pu 4+, Am 3+, and fission product elements such as Eu 3+, Sr 2+, Cs + . The results demonstrate the exceedingly high distribution ratios and favorable separation of Am 3+ and Pu 4+ in nitric acid media. All the three P5DGAs form 1 : 1 complexes with Am 3+ . Time resolved laser fluorescence spectroscopic (TRLFS) studies reveal a strong complexation involving no inner-sphere water molecules in the Eu 3+ –P5DGA complexes when C8 mimNTf2 is used as the diluent. With high efficiency in the extraction of actinides and a quantitative back extraction outcome, the RTIL-based solvent systems containing pillar[5]arene-DGA ligands developed in this work hold potential as promising candidates for nuclear waste remediation in a more sustainable fashion.